Towards a solution to the problem of safety management of structurally complex systems - Bochkov, Alexander V. (Journal of AppliedMath, 2023)
The non-isolation of modern, structurally complex, multi-purpose systems implies not only their interaction with the external environment, but also the impact of this environment on the systems themselves. The ability to predict and assess the consequences of these impacts, which are characterised by great uncertainty about the time, place and method of implementation, as well as the choice of a particular object of influence, is a task of extreme urgency in today’s globalised world. If the stability of functioning of any structurally complex system is understood as the achievement by it of the purpose of its functioning with acceptable deviations on the volumes and times of implementation of private tasks, the safety management in this system is reduced, in fact, to minimisation of unplanned losses at the occurrence of abnormal situations of various kinds and to carrying out of measures for their prevention. The success of such tactics depends largely on the effectiveness of the risk management system, on the ability of decision-makers to foresee the possibility of poorly formalised threats turning into significant risks, i.e., on having methods and tools for ranking threats and significant risk factors. Inevitably, there is the task of setting protection priorities, ranking objectives (usually of different types), problems and threats, and reallocating available (usually limited) resources. The article considers the issues involved in building an integral security model that takes into account the risks to the assets being protected.